If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying j + k = 3 Solving j + k = 3 Solving for variable 'j'. Move all terms containing j to the left, all other terms to the right. Add '-1k' to each side of the equation. j + k + -1k = 3 + -1k Combine like terms: k + -1k = 0 j + 0 = 3 + -1k j = 3 + -1k Simplifying j = 3 + -1k
| (6-5i)-5-4= | | 3d-7+12c=53 | | 2x+12=37 | | a+46/2=31 | | 100=0.16x | | y=2+48x^2+32x^4 | | 10z+6y=36 | | 80=0.8x | | 11+2x=55 | | 1.5=2r+(r-3) | | 8=-g | | 2x^2-5x-24=x^2 | | 19-5= | | 18y+10x=182 | | .6x-4y=54 | | 9+5=2y-4 | | x-12=3(x-18)-6 | | Logx=3.9 | | 3t^2-22t-16= | | 3x^2=41x | | 3x^2+8-116=0 | | 1874.25=1800(1+r*.75) | | (-5-4i)+(8+7i)= | | 3x^2+8x-116=0 | | 5(5c-1)-5=23c+2 | | sine(3x+50)=cosine(2x-10) | | 8720=8000(1+r*1) | | x^2+10y+16=0 | | 0.2x^3-6x^2=1000 | | sine(3x+50)-cosine(2x-10)=0 | | 5(c+8)whenac=6 | | 3x=6x-40 |